The Use of Small Group Discussion on Students' Speaking Skill at MA Al-Hidayah Bangkalan - Dwi Setyawan; Hafidz, Moh; Kurdi Wijaya, Moh (SELL (Scope of English Language Teaching, Linguistics, and Literature) Journal, 2024)
This study explore the use of small group discussion on students’ speaking skill. The issue identified by the researcher during this study is the lack of student participation in learning. As a result, the researcher conducted a study that involved both teachers and students in the learning process. The solution to address this problem was to employ group discussion strategies. Group discussions have proven to be highly effective for students in enhancing their speaking abilities, especially when speaking in public. This learning strategy heavily relies on student engagement, as in this approach, all aspects are decided and executed by the students. In conducting this research, the researcher utilized an approach called Observation and Interview. This research was proven to be effective in improving students' speaking skill